Lactate Detection in Tumor Cell Cultures Using Organic Transistor Circuits. Issue 13 (30th January 2017) - Braendlein, Marcel; Pappa, Anna‐Maria; Ferro, Marc; Lopresti, Alexia; Acquaviva, Claire; Mamessier, Emilie; Malliaras, George G.; Owens, Róisín M.
Abstract : A biosensing platform based on an organic transistor circuit for metabolite detection in highly complex biological media is introduced. The sensor circuit provides inherent background subtraction allowing for highly specific, sensitive lactate detection in tumor cell cultures. The proposed sensing platform paves the way toward rapid, label‐free, and cost‐effective clinically relevant in vitro diagnostic tools.